REKONSTRUKCJONISTYCZNA DESAKRALIZACJA TORY I JEJ WPŁYW NA WSPÓŁCZESNĄ KULTURĘ ŻYDOWSKĄ - Szczerbiński , Waldemar (Studia Europaea Gnesnensia, 2018)
The text is going to recognize the fact that in the world today it is culture which exerts a tremendous influence on how the Bible is understood by Jews themselves. This approach is exemplified in Jewish reconstructionism, which effected a veritable revolution in that respect. As it appears, the attitude has ultimately led to the desacralization of the Torah.